Collaborative regulatory development in the mobile money sector: A case study in Sri Lanka / Chaminda Methsiri Suwandaarachchi - Chaminda Methsiri , Suwandaarachchi (2020)
Providing financial services for the unbanked has been challenging, mainly due to relatively high operational costs and the difficulty of reaching remote areas. Mobile money has brought bank-like facilities to the unbanked communities, through its low-cost operations and widespread agent network, thus making them financially included. Regulatory response and support are essential for this advancement, where they necessitate significant changes to the current regulatory practices. This task is difficult for regulators due to their limited technical knowledge and resources in the field of financial technologies. Regulators collaborate with industry to overcome these challenges. However, studies on such collaborations are scarce. This study proposes a model for collaborative regulatory development for the mobile money industry.Actual practices were mapped with the theory of negotiated rule making to derive variations and extensions to the original theory. The study employed the case study research method, in particular, the Structured-Pragmatic-Situational (SPS) approach, for data collection and analysis. Regulators have appointed a discussion committee with a broader representation of interests, for more objective decision making. Further, the central bank has maintained close control throughout the negotiation process, where participants are motivated to compromise their interests to achieve joint gains. Findings reveal that the collaboration provided necessary knowledge and information for developing effective regulation, to participants. The central bank composed the executable rule, with the aid of information and knowledge gained through collaboration. Subsequent revisions also play an essential role in regulatory development. These revisions are developed through the involvement of stakeholders in the form of suggestions and comments. Collaborative testing and benchmarking are also similar joint approaches observed in mobile money regulation.